Effect of genetic modified maize contained Cry1Ab gene on the arthropods abundance and diversity in limited test field - Herlina, Lina; Istiaji, Bonjok (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
In Indonesia, transgenic products are still considered innovative, and genetically modified (GM) maize has stayed on the market while its impact on environmental biosafety is now being evaluated. Bt corn has been recognized as one of the solutions to the problem of Asian corn and cob borers to preserve maize production. Therefore, this study aimed to investigate the effect of Bt corn on arthropod richness and diversity in a limited testing field using a randomized block design with four different maize varieties as treatments in six replications. The significant findings showed that Bt corn had no significant influence on the diversity, evenness, and abundance index (Margalef and Meinhinick Index) in the limited testing fields, which were all greater at 85 days after plant (DAP) than 60 DAP. Based on the evenness and abundance index, we conclude that Bt corn does not harm the community of existing arthropods.